Code Switching and Code Mixing Found in the Novel Supernova: Ksatria, Puteri dan Bintang Jatuh by Dewi Lestari - -, Meilisa (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is a tool of communication from one person to another. They use English as one of the international language to be able to communicate with people from other nations. As we know, western culture has been spread in Indonesia especially in language terms. As a consequence, most of the Indonesian people use the variety of languages. The variety of language in Indonesia includes code switching and code mixing. The phenomenon of switching and mixing languages can be found in many aspects, for example in films, poems, songs, and novels. From this reason, the writer takes Supernova: Ksatria, Puteri dan Bintang Jatuh by Dewi Lestari novel as the object of this study because there are many code switching and code mixing terms of English and Indonesia used in this novel. This study investigated the types of code switching and code mixing which occur in the dialogues spoken by the main characters and the reasons why the characters switch or mix their dialogues. The writer used theories proposed by Hoffmann (1991). This study used a descriptive qualitative method because it provided description data. In addition, the writer described the type of code switching and code mixing of each utterance in the novel. The results showed from 108 utterances, 75 for Intra-sentential, 26 for Intersentential, four for intra-lexical, and three for establishing continuity with the previous speaker. It is because there are many of English terms that are familiar to them so that they can use in their utterances easily. The results also showed from 108 utterances, 26 utterances include reason talking about particular topic and eight other reasons also appear in the data. In conclusion, the writer found four types and nine reasons about the use of code switching and code mixing. The writer suggests the students of English Department to analyze code mixing and code switching in a movie or script. Besides, the next researcher can study more about other speech analysis such as presupposition and address terms.